Classifiers : a typology of noun categorization devices - Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna) (Oxford University Press, 2000)
This text offers a cross-linguistic account of classifiers. Its range of exemplification includes major and minor languages from every continent and several of the examples are from the author's own fieldwork.
Second series statement from jacket.
Keywords: Classifiers (Linguistics); Categorization (Linguistics); Grammar, Comparative and general -- Noun.; Classificateurs (Linguistique); Catégorisation (Linguistique); Nom (Linguistique); LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics.; Grammar, Comparative and general -- Noun; Classifiers (taalkunde); Naamwoorden.; Taaltypologie.